Two novel HLA class II alleles, DRB1*11:131 and DQB1*05:01:05, identified by sequence‐based typing. Issue 4 (27th August 2013) - Jakubauskas, A.; Valatkaite, B.; Griskevicius, L.
<x xml:space="preserve">Abstract</x> Two novel class II human leukocyte antigen alleles HLA‐DRB1*11:131 and HLA‐DQB1*05:01:05 are described.